Mi kering berbahan tepung kacang merah dengan pewarna buah naga sebagai pangan sumber serat - Khalidza, Wafiq Noor; Susilowati, Prima Endang; Ghaffar, Mufti (Nutrition Scientific Journal, 2025)
Noodles are one of the types of food favored by the public. Most noodles available on the market are made from wheat flour, which is high in starch and low in fiber. An alternative is to replace the ingredients with those that have higher nutritional value. Red beans and dragon fruit offer nutritional benefits, including high fiber content and antioxidants. This study aims to evaluate the acceptability, fiber content, and starch content of dried noodles substituted with red bean flour and colored with dragon fruit juice. This research used a Completely Randomized Design (CRD) with four formulations and three replications. The noodle formulations were made by combining red bean flour and dragon fruit juice with the following wheat flour to red bean flour ratios: 100:0 (F0), 80:20 (F1), 70:30 (F2), and 60:40 (F3). The data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney post hoc test. Crude fiber content was analyzed using the gravimetric method, and starch content was analyzed using the AOAC (1970) method. Organoleptic testing results showed significant differences in aroma, color, taste, and texture indicators. Formula F1 was the most preferred formulation, with the highest average scores across the four evaluation criteria. The analysis of the selected formula (F1) showed it contained 2.69 g of crude fiber per 100 g of dried noodles and 74.28 g of starch per 100 g of dried noodles. It is concluded that Formula F1 can be considered a fiber-rich food. This study recommends consuming the dried noodles along with other fiber-rich foods to meet daily fiber requirements.